Level of service quality provided by Bank Rakyat Bandar Baru Bangi / Norhishamudin Mohamed - Mohamed, Norhishamudin (Faculty of Business and Management, 2010)
This researches paper is about a study on quality service that lead to customer satisfaction towards the service provide by Bank Rakyat Bandar Baru Bangi. The objectives of the study are to identify the most important dimension of service quality and to determine the ranking of the service quality dimension perceived by the customer that lead to the customer satisfaction toward services provided by the Bank Rakyat Bandar Baru Bangi. In this study, the primary and secondary data will be used. This is including the interview, questionnaires, journals, books, and articles. In the end of this study, the researchers conclude that the most important dimension of service quality is assurance because have the highest means compare to another dimensions. The highest mean is the highest ranking and the lowest ranking is the lowest ranking. It can be concluded that the ranking of service quality dimension that perceived by the customer that lead to their satisfaction towards the services provided by Bank Rakyat Bandar Baru Bangi are assurance, tangibles, responsiveness, reliability and empathy.